Sequence analysis of select terpene synthase genes in Philippine coffee - Mondragon, Miguel V.; Santos, Daisy May C. (Philippine journal of science)
"Aroma is one of the factors used to evaluate coffee quality. Aroma profile differences between coffee varieties are dictated by the unique and diverse combination of volatiles, such as terpenes. Several studies have elucidated the phylogenetic relationships of coffee varieties using various DNA markers; however, this is the first study to directly compare DNA sequences of their terpene synthase (TPS) genes, specifically in Philippine coffee samples" - title page.